Left Ventricular Flow Distribution as a Novel Flow Biomarker in Atrial Fibrillation - Kim, Hansuk; Sheitt, Hana; Wilton, Stephen B.; White, James A.; Garcia, Julio (Frontiers in Bioengineering and Biotechnology, 2021)
Introduction: Four-dimensional flow (4D flow) cardiac magnetic resonance imaging can be used to elegantly describe the hemodynamic efficiency of left ventricular (LV) flow throughout the cardiac cycle. Patients with non-valvular paroxysmal atrial fibrillation (PAF) may have occult LV disease. Flow distribution analysis, based on 4D flow, may unmask the presence of LV disease by assessing flow components: direct flow, retained flow, delayed ejection, and residual volume. This study aimed to identify LV hemodynamic inefficiencies in patients with PAF and normal systolic function. We hypothesized that the fraction of direct flow to the total end-diastolic volume would be reduced in patients with PAF compared to controls. Methods: We used 4D LV flow component analysis to compare hemodynamics in 30 healthy controls and 50 PAF patients in sinus rhythm. Results: PAF subjects and healthy controls had similar LV mass, volume and ejection fraction. Direct flow was lower in the PAF group than in the controls (44.5 % ± 11.2 % vs 50.0 % ± 12.2 %, p=0.042) while delayed ejection was higher in the PAF group (21.6 % ± 5.6 % vs 18.6 % ± 5.7 %, p=0.022). Conclusion: PAF patients demonstrated a relative reduction in direct flow and elevation in delayed ejection.